Sei sulla pagina 1di 9

A =

3 1 B =

1

1

0

5

R 3

A =

3

1

1

 

 

B A =

2

1

4

r =

3

1

1

+

2

1

4

x

y

z

 

    + λ

x

y

z

=

3

1

1

2

1

4

,

λ R

x

y

z = 1 + 4λ

3 + 2λ

= = 1 + λ

.

λ

 x = 3 + 2 (y − 1) λ = y − 1

z = 1 + 4 (y 1)

λ

= 0

4y z 5 = 0

x 2y 1

.

n

R 3

R 3

R 3

B A P A

P

=

x

y

z

(P A) × (B A)

x

y

z

3

1

+ 1

×

2

1

4

= 2 (z + 1) + 4 (x 3)

4 (y 1) + z + 1

x + 3 + 2 (y 1)

=

4y + z + 5 4x 2z 14 x + 2y + 1

=

= 0

2x z 7 = 0

x 2y 1 = 0

4y z

5

.

II = 2III + I

4y z 5 = 0

x 2y 1 = 0

.

x z y

 z = 4y − 5 x = 2y + 1 . x = 2y + 1 y = y , z = 4y − 5 x = 1 + 2t y = t , z = −5 + 4t

t R

   B

2

1

4

=

1

0

5

A t λ t = λ + 1

t

R 2

S 1 =

x y R 2 |x 2 + y 2 = 1

S 1

S 1 R 2

S 1

R 2 R 2 R 2 S 1 R 2 S 1

S 1 R 2

S 1 R 2 S 1

0 2 + 0 2

=

1

S 1 = α 1 v 1 +

+

α n v n ,

v 1 ,

,

v n S 1 , α 1 ,

, α n R,

n N >0 .

S 1 S 1 S 1

v S 1 α

= ±1 αv / S 1

αv = |α| v = |α| v = 1

v S 1 S 1 αv R 2

R 2 S 1

S 1 = R 2 S 1 R 2

v 1 ,

,

v m := {v 1 ,

,

v m }

S 1 = R 2 R 2 S 1 e 1 e 2 R 2 S 1 R 2 S 1 = R 2

R 4

=

1

0

1

0

,

2

1

0

1

,

1

1

1

1

,

0

2

1

1

W

W

W

a, b, c, d R

a

1

0

1

0

+ b

2

1

0

1

+ c

1

1

1

1

+ d

0

2

1

1

=

0

0

0

0

a, b, c, d

 

 

a + 2b + c = 0

b + c + 2d = 0 a c d = 0

b + c + d = 0

 

 

 

 

a + 2b + c = 0

b + c + 2d = 0

a + c + d = 0

a + b = 0

a + 2b + c = 0

b + c + 2d = 0

a + c + d = 0

a = b

a = b

b + 2b + c = 0

b + c + 2d = 0

b

a

+ c + d = 0 = b

c

b + c + 2d = 0

b + c + d = 0

a = b

= 3b

c = 3b

 

 

c = 3b

b 3b + 2d = 0

b 3b + d = 0

a = b

= 3b

c

2d = 4b

d

a

= 2b

= b

a

c

d

= b

= 3b

= 2b

b a = b = 1 c = 3 d = 2 v 1 , v 2 , v 3 , v 4 W

v 1 + v 2 3v 3 + 2v 4 = 0,

v 1 = v 2 + 3v 3 2v 4 v 1 W = v 2 , v 3 , v 4

v 2 , v 3 , v 4

 

b

2

1

0

1

 

+ c

1

1

1

1

 

+ d

 

0

2

1

1

 

=

0

0

0

0

 

.

2b + c = 0

b + c + 2d = 0 c d = 0

b + c + d = 0

a = 0

a = 0 b = 0

c = d = 0

v 2 , v 3 , v 4 B W

v 2 , v 3 , v 4

b

=

c = d

= 0

B =

2

1

0

1

,

1

1

1

1

,

0

2

1

1

W W

 

 

x 1 = 2α + β

x 2 = α + β + 2γ

x 3 = β γ

x 4 = α + β + γ

α, β, γ

,

dim W = 3 4 3 = 1 W β

  = x 1 2α

α + x 1 2α + 2γ

β

  x 1 + 2α γ

x 2 =

x 3 =

  x 4 = α + x 1 2α + γ

 

 

β = x 1 2α

x

x

x 4 = α + x 1 + γ

 = −3α + x 1 + 2γ = −x 1 + 2α − γ

2

3

β β α

x

2

=

3 (x 1 x 4 + γ) + x 1 + 2γ

x 3 = x 1 + 2 (x 1 x 4 + γ) γ

α = x 1 x 4 + γ

= 2x 1 + 3x 4 γ

x

x 3 = x 1 2x 4 + γ

α = x 1 x 4 + γ

2

α

x 2

= 2x 1 + 3x 4 γ

x 3 = x 1 2x 4 + γ

γ

γ = 2x 1 x 2 + 3x 4 x 3 = x 1 2x 4 2x 1 x 2 + 3x 4

γ = 2x 1 x 2 + 3x 4 x 1 + x 2 + x 3 x 4 = 0

W

x 1 + x 2 + x 3 x 4 = 0

2α + β α + β + 2γ β γ α β γ = 0,

0 = 0

W

w u

λ, µ C λw + µu = 0 λ = 0 µ u λ

w

= 0

α := µ α C µ

0 w = µ u

w u

W, U

V

=

= W U

0

u

=

0

V

w

u

U

w

λ

=

λ

λ C λ

λ

w = αu u U U αu U w U w W U w W U W U

W U = {0} w = 0 w

= 0

w u